2013
DOI: 10.1113/jphysiol.2013.254722
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metaboreflex and autonomic regulation of heart rate in humans

Abstract: Key points• Heart rate increases during exercise due to withdrawal of cardiac parasympathetic tone and increased cardiac sympathetic nerve activity.• We investigated the autonomic mechanisms whereby heart rate is regulated by the activation of metabolically sensitive skeletal muscle afferents (muscle metaboreflex).• Heart rate responses elicited by partial flow restriction during leg cycling (enhanced metaboreflex activation) and post-exercise muscle ischemia following leg cycling and handgrip (isolated metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 53 publications
4
75
0
9
Order By: Relevance
“…Intriguingly, HR variability analysis indicates that elevations in HR during postexercise ischemia following leg cycling are associated with reductions in cardiac parasympathetic activity (128). However, pharmacological investigations have shown that this HR elevation persists with either muscarinic or β-adrenergic blockade, implying a redundancy in the sympathetic and parasympathetic control of the heart under these conditions (83). The role of the muscle metaboreflex in cardiac autonomic control has also been evaluated by the occlusion or partial occlusion of perfusion to the exercising skeletal muscles.…”
Section: Skeletal Muscle Metaboreflex During Steady-state Exercisementioning
confidence: 96%
See 1 more Smart Citation
“…Intriguingly, HR variability analysis indicates that elevations in HR during postexercise ischemia following leg cycling are associated with reductions in cardiac parasympathetic activity (128). However, pharmacological investigations have shown that this HR elevation persists with either muscarinic or β-adrenergic blockade, implying a redundancy in the sympathetic and parasympathetic control of the heart under these conditions (83). The role of the muscle metaboreflex in cardiac autonomic control has also been evaluated by the occlusion or partial occlusion of perfusion to the exercising skeletal muscles.…”
Section: Skeletal Muscle Metaboreflex During Steady-state Exercisementioning
confidence: 96%
“…Unlike postexercise ischemia, however, this maneuver engages the muscle metaboreflex whilst central command and muscle mechanoreceptors are also activated. Experimental hypoperfusion in exercising dogs (238) and humans (83) can evoke a robust increase in HR that is attenuated by β-adrenergic blockade and not affected by cardiac parasympathetic blockade. However, as β-adrenergic blockade does not entirely block this response (83,238) and as HR variability derived estimates of cardiac parasympathetic activity are reduced during leg cycling with restricted flow (128), the ability of the muscle metaboreflex to inhibit cardiac parasympathetic activity cannot be entirely ruled out.…”
Section: Skeletal Muscle Metaboreflex During Steady-state Exercisementioning
confidence: 99%
“…It has been shown that subjects must make a greater effort to perform the same amount of work when blood flow to exercising muscles is restricted (14,19,30). In such situations, the reduced blood flow and resultant accumulation of metabolites would cause muscle fatigue, and recruitment of additional motor units would be required to maintain the same force.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reduced blood flow and resultant accumulation of metabolites would cause muscle fatigue so that recruitment of additional motor units would be required to perform the same amount of work, and thus central command would be increased (12,14,19,30). It has been demonstrated in dogs that reducing hindlimb blood flow to ϳ50% of the free flow level during mild treadmill running elicits a systemic pressor response (5,18,25,51).…”
mentioning
confidence: 99%
“…The first protocol involved isometric handgrip (n ϭ 9) and the second leg cycling exercise (n ϭ 8). Records were analyzed from previous studies (15,16) testing different hypotheses for which experimental protocols and procedures were approved by the local ethics committee (H-B-2009-024, H-3-2011-101) and undertaken in accordance with the Declaration of Helsinki. In these studies, the responses to the onset of exercise were not analyzed.…”
Section: Methodsmentioning
confidence: 99%